Protecting human and ecological health under viral threats in Asia - Matsui, S (Water science and technology : a journal of the International Association on Water Pollution Research, 2005)
Severe acute respiratory syndrome (SARS) outbroke in 2003, and the avian influenza A (H5N1) also outbroke in 2003 and continued to 2004. These pandemic viral diseases originated in South East Asia. Many human and animal lives were lost. Economic damages due to the pandemics were also very large. The question arises of why did the pandemics originate from South East Asian areas. Human influenza A consists of many sub-types of coronaviruses including the SARS virus and the avian influenza (H5N1) that are all variants of RNA of avian coronavirus. Variants are formed during infection of a coronavirus through not only birds but also mammals, including human beings. There are hot spots where viral infection rates are accelerated among birds, mammals and human beings. Suspicious areas are in South East Asia, where living conditions of birds, mammals and human beings are so close that there are always risks of viral infection. When we see the living conditions of farmers in southern China, northern Vietnam, Laos and northern Myanmar, they commonly raise ducks/chickens with pigs sharing ponds into which they discharge household wastewater, including human excreta, and pig excreta that are significant carriers of viruses. Bird faeces are also key carriers of the viruses. In the ponds, they raise ducks and conduct fish culture. Other important players are migrating birds from North Asia, which are principal vectors of avian influenza viruses. There is an urgent necessity of improving human and ecological health in South East Asia to control viral infection among birds, mammals and human beings. We can hinder the vicious cycle of virus infection through water contamination in ponds by providing good human, pig and chicken sanitation. It is easy to provide good sanitation practices for human, pigs and chickens, introducing collection and treatment of excreta. Our modern water technology can find good solutions for the problem